Construction and Application of GIS-Based Public Transport Transfer Network - Hang Su; Leishan Guo; Yunpeng Li; Shijie Liu; Junde Fan; Cong Du; Jianqing Wu (IEEE Access)
The transfer issue has always been a hot topic in the field of public transport, and improving transfer efficiency is crucial for effectively guiding public travel and optimizing the organization of public transportation. This paper proposes a new method for constructing transfer networks based on the advantages and disadvantages of the Space-P model and network analysis methods. Taking Lhasa as a case study, we used ArcGIS software to construct the public transport transfer network of Lhasa and employed network analysis methods to validate the effectiveness of the constructed transfer network. Based on 851 bus stops in the study area, a total of 723,350 valid routes were obtained. According to the validation results, after data organization and spatial representation using ArcGIS, the constructed transfer network can effectively measure passenger dwell time, transfer coefficients, and transfer routes in the public transport network, demonstrating the network’s effectiveness. This paper aims to provide a new perspective for the construction of public transport transfer models and offers scientific basis for the planning and design of public transport systems.